Efficiency of common bean genotypes in response to nitrogen fertilization - Salgado, Fabricio Henrique Moreira (2012)
Bean genotypes react differently to available nitrogen. This research aimed at selecting bean genotypes, concerning their efficiency and reaction to nitrogen absorption. The treatments consisted of twelve genotypes cultivated in two different environments, one simulating a low nitrogen level (20 kg ha-1) and the other a high nitrogen level (120 kg ha-1). The experimental design was randomized complete bocks, with four replications. The grain yield was evaluated, for classifying cultivars in relation to nitrogen use efficiency and response to application, as well as chlorophyll rates, by using a chlorophyllometer. The BRS-Grafite and Princesa genotypes were considered efficient, regarding the nitrogen fertilization, and responsive to the nitrogen application. Bean plants supplied with adequate nitrogen rates presented higher cholorophyll (a, b and total) levels.